EFEKTIVITAS PENERAPAN PAJAK DIGITAL PADA E-COMMERCE - Marchia Dwi Harmada Simanjuntak; Monalisa Lusiana Piliang; Nabila Muzakia; Risya Maulida; Priska Rahel Naibaho (Nindikayla Institute, 2026)
The development of e-commerce in Indonesia has experienced rapid growth in recent years. This situation has prompted the government to implement a digital tax policy as an effort to create tax fairness and increase state revenue from digital economic activities. This study aims to analyze the effectiveness of implementing digital taxes on e-commerce activities, particularly in terms of taxpayer compliance, increasing state revenue, and its impact on digital businesses. The research method used is a qualitative approach using literature studies and analysis of various digital tax regulations in force in Indonesia. E-commerce taxes raise various issues, particularly related to the fairness gap with conventional merchants, opportunities for tax avoidance, and the compliance burden on MSMEs. Policies such as the Minister of Finance Regulation (PMK) concerning tax collection through marketplaces often generate pros and cons. Therefore, the effectiveness of taxes in the e-commerce sector is important to examine. This effectiveness can be seen from the extent to which tax policies are able to increase compliance of digital businesses, optimize state revenue, and create a fair tax system that is in line with the development of the digital economy in Indonesia.